An Experiment on Diversification and Path Dependence. Issue 2 (3rd April 2021) - Kluger, Brian; Miele, Jennifer
Abstract: In an experiment where subjects can allocate their wealth between cash and two risky assets, we analyze path-dependent portfolio choices. The experiment is designed to isolate cases where subjects have no prior experiences, and cases where subjects experience isolated changes in wealth or relative prices. We find that subjects tend to be less diversified after wealth or relative price changes, but that the result is much stronger for relative price changes. This erosion in portfolio diversification after relative price changes mainly stems from the choices of subjects with more diversified positions when there are no prior experiences.